Trends in the Use of Augmented Reality from Tangible Interfaces in School Learning : A Systematic Literature Review - Indrawan, I Putu Eka; Agustini, Ketut; Dantes, Gede Rasben; Sudhata, I Gde Wawan (Jurnal Paedagogy, 2024)
This study aims to analyze trends in the use of augmented reality from tangible interfaces in the context of formal and informal education. This study employed a systematic literature review (SLR) method adapted from the PRISMA model. This research used the Publish or Perish application to search for various relevant scientific articles taken from international journals, Scopus, with a range of 2019-2023. The data analysis technique for this research used thematic analysis. The development of AR media showed significant improvement, especially in the aspect of increasingly realistic and diverse user interfaces, enabling closer integration with the curriculum and presenting more engaging learning experiences. The interactive and collaborative features of AR applications showed great potential for enhancing student interaction with learning materials through immersive and interactive visual experiences. In addition, such collaborative features could also facilitate cooperation between students, creating a more dynamic and effective learning environment in schools. This research emphasized the importance of using appropriate research methods to deepen the understanding of the development of AR media in education and the potential of AR applications in creating more interactive and collaborative learning experiences in school environments.